The 4G/5G polymorphism of plasminogen activator inhibitor type 1 is a predictor of allergic cough - Tang, Rui; Lyu, Xiaohong; Li, Hong; Sun, Jinlyu (Frontiers in Genetics, 2023)
Background: It has been suggested that genetic factors may be substantially linked to allergy disorders. This study aims to investigate the relationship between the genetic susceptibility of Chinese patients with allergy disorders and the polymorphisms of PAI-1 rs1799762, CYSLTR1 rs320995, GSDMB rs7216389, GPIIIa rs5918, GP1BA rs6065, PEAR1 rs12041331, and TNF-α rs1800629. Methods: From the Peking Union Medical College Hospital, this study enrolled 60 healthy participants and 286 participants with allergic diseases. TaqMan-MGB (minor groove binder) qPCR was used to examine the gene polymorphisms for PAI-1 rs1799762, CYSLTR1 rs320995, GSDMB rs7216389, GPIIIa rs5918, GP1BA rs6065, PEAR1 rs12041331 and TNF-α rs1800629 in each group. Results: The TaqMan-MGB qPCR results were completely consistent with the DNA sequencing results, according to other studies in this medical center (Kappa =1, P<0.001). Only the distribution of PAI-1 rs1799762 was different between allergic illness patients with cough and healthy people (χ2 =7.48, P=0.0238). With regard to cough patients, the 4G4G and 5G5G genotypes were more frequent (allergic cough vs healthy individuals: 4G4G 57.9% vs 26.7%; 5G5G 20.0% vs 13.3%), but the 4G5G genotype was more frequent in healthy people (allergic cough vs healthy individuals: 45.7% vs 60.0%). The CYSLTR1 rs320995, GSDMB rs7216389, GPIIIa rs5918, GP1BA rs6065, PEAR1 rs12041331 and TNF-α rs1800629 polymorphisms, however, did not show any such relationships. Conclusion: The PAI-1 rs1799762 polymorphisms may be associated with the genetic susceptibility of Chinese allergic disease patients with cough performance.